2015
DOI: 10.1158/1055-9965.epi-14-0934
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Intrinsic Subtype Is Reflected in Cancer-Adjacent Tissue

Abstract: Introduction Overall survival of early-stage breast cancer (BC) patients is similar for those who undergo breast conserving therapy (BCT) and mastectomy, however, 10-15% of women undergoing BCT suffer ipsilateral breast tumor recurrence. The risk of recurrence may vary with BC subtype. Understanding the gene expression of the cancer-adjacent tissue and the stromal response to specific tumor subtypes is important for developing clinical strategies to reduce recurrence risk. Methods We utilized two independent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 50 publications
2
60
3
Order By: Relevance
“…The 20 micron section width was selected to maintain tissue integrity from non-fixed tissues and to ensure histologically-representative samples as very few samples were unable to produce viable sections at 20 micron width. The central portion of the tissue specimen was used for nucleic acid extraction as described elsewhere(7). If frozen specimens were not available (2.0% of patients), paraffin-embedded tissues were used for sectioning and digital annotation.…”
Section: Methodsmentioning
confidence: 99%
“…The 20 micron section width was selected to maintain tissue integrity from non-fixed tissues and to ensure histologically-representative samples as very few samples were unable to produce viable sections at 20 micron width. The central portion of the tissue specimen was used for nucleic acid extraction as described elsewhere(7). If frozen specimens were not available (2.0% of patients), paraffin-embedded tissues were used for sectioning and digital annotation.…”
Section: Methodsmentioning
confidence: 99%
“…We compared gene expression in normal ( RM) , cancer-adjacent normal and tumor ( UNC337 + NKI295 ) datasets. Reduction mammoplasty samples were from previous reports [10, 11] and from the Normal Breast Study, a study of patients undergoing surgery at UNC Hospitals [12]. All patients provided informed consent via a protocol approved by the Institutional Review Board of the University of North Carolina at Chapel Hill.…”
Section: Methodsmentioning
confidence: 99%
“…Gene network analysis predicted activation of TNF-a/IFNg signaling pathways in immune-enabled tumors and activation of the transforming growth factor-b (TGF-b) pathway in immunedisabled tumors. 13 Gene expression studies of BC-adjacent tissues showed that the TNBC microenvironment had increased expression of genes involved in inflammation 14 and revealed further subtypes, some with a low immune response defined by a minimal T cell infiltrate and effector function, and high frequency of suppressive M2-like macrophages, and others with a high immune response and low frequency of M2-like macrophages. 15 These data imply that communication between tumor cells and other cells in cancer-adjacent tissue contributes to BC progression and/or metastasizing potential; the same is likely to be true for Luminal B BC (Fig.…”
Section: Breast Cancer and Immunitymentioning
confidence: 99%